Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3847/1538-4357/836/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Two New Calcium-rich Gap Transients in Group and Cluster Environments

Abstract: We present the Palomar Transient Factory discoveries and the photometric and spectroscopic observations of PTF11kmb and PTF12bho. We show that both transients have properties consistent with the class of calcium-rich gap transients, specifically lower peak luminosities and rapid evolution compared to ordinary supernovae, and a nebular spectrum dominated by [Ca II] emission. A striking feature of both transients is their host environments: PTF12bho is an intracluster transient in the Coma Cluster, while PTF11km… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 82 publications
10
111
0
Order By: Relevance
“…The lower panel of Fig. 9 shows the +12.9 and +19.6 d spectra of SN 2019bkc compared to the same sample of Ca-rich nebular phase spectra, with the addition of PTF12bho (Lunnan et al 2017). The emission lines at ∼7000 and ∼8400 Å seen in the spectra of SN 2019bkc look similar to those seen in the Ca-rich events (and associated with [Ca ii] and Ca ii, respectively).…”
Section: The Extraordinary Ca-rich Early Nebular Phasementioning
confidence: 73%
“…The lower panel of Fig. 9 shows the +12.9 and +19.6 d spectra of SN 2019bkc compared to the same sample of Ca-rich nebular phase spectra, with the addition of PTF12bho (Lunnan et al 2017). The emission lines at ∼7000 and ∼8400 Å seen in the spectra of SN 2019bkc look similar to those seen in the Ca-rich events (and associated with [Ca ii] and Ca ii, respectively).…”
Section: The Extraordinary Ca-rich Early Nebular Phasementioning
confidence: 73%
“…The helium WD TDE light curves show similar timescales and luminosities to calcium-rich transients (Perets et al 2010;Kasliwal et al 2012;Valenti et al 2014;Lunnan et al 2017;Milisavljevic et al 2017;De et al 2018), .Ia explosions (Kasliwal et al 2010;Shen et al 2010), and rapid transients recently discovered by Drout et al (2014); Pursiainen et al (2018). We compare our models with observed transients of these classes.…”
Section: Possible Observational Counterpartsmentioning
confidence: 77%
“…Ivanova et al (2006) demonstrated similar results regarding the contribution of cluster WDs to the Type Ia SNe rate. WD-NS collisions in GCs have been proposed as a possible mechanism of calcium-rich gap transients observed at high radial off-sets in metal-poor galaxies (Kasliwal et al 2012;Lunnan et al 2017;De et al 2018;Shen et al 2019). Additionally, tidal disruptions of WDs by BHs (especially IMBHs) in GCs have been examined in several analyses (Rosswog et al 2009;MacLeod et al 2016;Fragione et al 2018b).…”
Section: White Dwarfs Collisions -Connecting To High-energy Transientsmentioning
confidence: 99%